Margaret Thatcher and Ronald Reagan - Cooper, J. author. aut Link
X, 261 p.
Keywords: A new exploration of the relationship between the Margaret Thatcher and Ronald Reagan administrations in domestic policy. Using recently released documentary material and extensive research interviews, James Cooper demonstrates how specific policy transfer between these 'political soul mates' was more limited than is typically assumed.